The consequences and mitigation of floods affecting Taman Sri Muda, Shah Alam / Muhamad Anas Amsyar Muhamad Azizi and Suharto Teriman - Muhamad Azizi, Muhamad Anas Amsyar; Teriman, Suharto (2023)
This study aims to identify the contributing factors of floods in Taman Seri Muda, Shah Alam and suggest suitable mitigation approaches to prevent future floods in the area. The study collects data through on site observation and questionnaire survey from homeowners affected by the floods. Data were analysed quantitatively. Results indicates that the floods were caused by multiple factors namely prolonged heavy downpour, clogged drains and high water tides which prevents water from flowing out to the Klang River. More than 40% respondents had experienced floods more than four times in the area. The floods also caused physical damages to their properties and left them with huge financial losses. Recommendations to risk of similar disaster include conducting periodic inspections and maintenance of monsoon drains, and using advanced weather tracking systems that help predict and prepare for impending floods, allowing authorities to issue timely warnings.